Dewan Pengawas Syariah dalam Sistem Hukum Perbankan: Studi Tentang Pengawasan Bank Berlandaskan Pada Prinsip-Prinsip Islam (Lex Jurnalica, 2008)
Capitalist economy decline that apply free market basis and socialist economy with country control in economics according to centrally, be points stands on for syariah economy development. Basis that putted in syariah economy justice or right equivalence and duty, begation all kind of repression or penggerogotan towards other party, with has dimension sosiologis. While syariah economics principal pillar syariah banking. finance crisis existence and banking has given lesson that syariah banking system obvious has stamina has faced crisis and this matter has pushed more the intensiveer sharia banking development actually begun in the year 1992 with operatives law no. 7, 1992 about banking. Syariah banking special characteristics needs handling aloof in arrangement and supervision, with socialization syariah supervisor council. DPS be a body that founded and laided in bank that do business activity based on syariah principle to ascertain that syariah bank operational doesn't deviate from syariah principles and as special supervisor in transaction follows islam law.Keywords: Syariah Banking, Islamic Bank, DPS